The Business Service Sector in India, Ireland and Poland. A Comparative Analysis - Arkadiusz Mroczek (Comparative Economic Research. Central and Eastern Europe, 2019)
The fast growth of the service sector is one of the characteristic features of the contemporary economy. Amongst other CEE countries, Poland is one of the emerging locations for this sector. The aim of the paper is to examine and compare the business service sector in India, Ireland and Poland. Both India and Ireland are exceptional locations for this industry, so comparing the state and operating conditions in Poland with those countries can be insightful. A literature study is used to determine the motives of companies undertaking offshore investments, upon which a selection of location factors is made. In the empirical part, those factors are analyzed in a descriptive way. This allows us to draw conclusions concerning this sector in Poland. This country, to some extent, possesses selected positive features of both India and Ireland, which explains the current growth of the sector.
Keywords: F21; F23; O32; 330; Business Process Outsourcing; Business Service Sector; BPO; SSC; location choice